2002
DOI: 10.1093/geronb/57.1.s3
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocity in Parent-Child Relations Over the Adult Life Course

Abstract: The results offer some support for investment, insurance, and altruistic models of intergenerational exchange. Sharing time in activities provides a direct return to the parent that is characteristic of an investment strategy, whereas financial transfers provide a time-contingent return that is characteristic of an insurance mechanism. That affection triggers greater support to more functionally impaired mothers suggests that emotionally investing in children as a health insurance mechanism may be based on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
307
1
19

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 362 publications
(349 citation statements)
references
References 32 publications
22
307
1
19
Order By: Relevance
“…Financial help from and coresidence with parents are associated with greater support to parents later in life (Leopold, 2012;Silverstein, Conroy, Wang, Giarrusso, & Bengtson, 2002), indicating reciprocity between parents and children over the life course. An ample body of research shows support from adult children to their older parents, usually in the context of very old age, declining health, and widowhood of the older parent (Seltzer & Friedman, 2013;for review, see Connidis, 2010).…”
Section: Intergenerational Ties: Inside Familiesmentioning
confidence: 99%
“…Financial help from and coresidence with parents are associated with greater support to parents later in life (Leopold, 2012;Silverstein, Conroy, Wang, Giarrusso, & Bengtson, 2002), indicating reciprocity between parents and children over the life course. An ample body of research shows support from adult children to their older parents, usually in the context of very old age, declining health, and widowhood of the older parent (Seltzer & Friedman, 2013;for review, see Connidis, 2010).…”
Section: Intergenerational Ties: Inside Familiesmentioning
confidence: 99%
“…Parent-child contact frequency has also been shown to be higher if parental investments during childhood were larger in terms of time (Grundy 2005;Silverstein et al 2002) or affection (Downey 1995;Kaufman and Uhlenberg 1998).…”
Section: Dyadic Contact Within Networkmentioning
confidence: 99%
“…It should be mentioned though, that in earlier research on intergenerational support the effect of direct reciprocity remained intact when controlling for these types of potential underlying factors (Klein Ikkink et al, 1999). Also no information was available about the level of support parents provided to their children earlier in life (Silverstein et al, 2002) and therefore it was not possible to test the notion of long-term reciprocity.…”
Section: Discussionmentioning
confidence: 95%
“…The norm of reciprocity reduces uncertainty and ensures that if people give something, they will always receive something in return (Gouldner, 1960). Among parents and their children this is not, however, necessarily the same kind of support nor does it have to be exchanged at the same moment in time (Silverstein, Conroy, Wang, Giarrusso, & Bengtson, 2002). Research has shown that parents who give support to their children are more likely to receive help from them in return (e.g., Grundy, 2005; Klein Ikkink, Van Tilburg, & Knipscheer, 1999).…”
Section: Theoretical Backgroundmentioning
confidence: 99%